Pengaruh: PAD, DAK, DBH, ,SiLPA dan flypaper effect terhadap perilaku oportunistik penyusun anggaran - Febrianti, Yolinda Lisa; Suparwati, Yohana Kus (Nur Science Institute, 2021)
The implementation of the regional autonomy policy has brought changes to the regional government system, which has implications for the increasing role of the executive in making public policies, especially those related to regional budgeting. The regional autonomy policy is a gap for budget makers to act opportunistically. Opportunistic behavior is an act of seeking self-interest by using deception. This study aims to determine the effect of regional original revenue, special allocation funds, revenue sharing funds, SiLPA, and flypaper effects on opportunistic behavior in budgeting. The sample was taken from the provincial government in Indonesia by purposive sampling method. The test tool uses multiple linear regression. The study results found that the special allocation fund, SiLPA, and flypaper effect affected opportunistic behavior in budgeting. In contrast, regional original revenue and revenue sharing funds did not affect opportunistic behavior in budgeting.